2020
DOI: 10.3389/feduc.2020.00005
|View full text |Cite
|
Sign up to set email alerts
|

Conflict in the Classroom: How Teachers’ Emotional Intelligence Influences Conflict Management

Abstract: Distinct studies showed a positive relationship between emotional intelligence and conflict management. However, there is a lack of research on how teachers' emotional intelligence influences conflict management in the classroom. Since much more needs to be learned about how teachers' emotional skills related to classroom practice, this research has emerged, and the purpose went to examine how teachers' emotional intelligence influences classroom conflict management. Moreover, the relationship between gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 35 publications
2
52
0
8
Order By: Relevance
“…The research results show that EI offers opportunities for conflict resolution. This conclusion is in line with the results of Valente & Lourenço (2020) who confirmed that EI teachers have greater commitment levels for conflict resolution.…”
Section: Discussionsupporting
confidence: 91%
“…The research results show that EI offers opportunities for conflict resolution. This conclusion is in line with the results of Valente & Lourenço (2020) who confirmed that EI teachers have greater commitment levels for conflict resolution.…”
Section: Discussionsupporting
confidence: 91%
“…Among the variables that influence the choice of different conflict management strategies, the teachers' emotional intelligence stands out. Valente and Lourenço [24] conclude that teachers who tend to have higher levels of emotional intelligence use more integration and commitment strategies, for conflict management in the classroom, and fewer strategies of consent, avoidance, and domination. Too, the findings of Aliasgari and Farzadnia [29] indicate that teachers prefer the integrating strategy over the other conflict management strategy.…”
Section: Strategies For Classroom Conflict Managementmentioning
confidence: 99%
“…There are many and diverse classroom conflict situations that disturb the class dynamics. And in situations where the conflict remains latent, the result of the diversity of class interests, if the teacher does not create a good environment, acting positively about communication, the use of legitimate authority, and the conflict management, he will see conflicts increase exponentially within the classes [24]. Thus, regardless of the classroom conflicts type, if they are not managed, they accumulate, which makes them more cohesive and complicated, triggering negative feelings in those involved, and negatively affecting the educational quality [24].…”
Section: Conflict In the Classroommentioning
confidence: 99%
See 2 more Smart Citations